Effects of Different Drying Methods on the Structure and Quality of Pleurotus eryngii - Jiankai CHEN (Shipin gongye ke-ji, 2023)
In order to explore the effects of different drying methods on the microstructure and quality of dried products of Pleurotus eryngii, five methods were selected to dry the dried products: Hot air drying, microwave vacuum drying, intermittent microwave vacuum drying, hot air-microwave combined drying and vacuum freeze-drying , and the micromorphology, shrinkage rate, rehydration ratio, color, amino acid content, polysaccharide content and sensory evaluation of dry products were used as evaluation indexes. The results showed that vacuum freeze-drying was the best to maintain the integrity of tissue structure, with the smallest shrinkage rate (30.2%), the largest rehydration ratio (3.03), and the best recovery effect, the highest polysaccharide content (13%). The amino acid (560.94 mg/100 g) and sensory evaluation (9.4 points) of hot air-microwave combined drying were the highest, and the shrinkage rate (55.43%), rehydration ratio (1.83), color (76.29) and polysaccharide (11.8%) were the second highest after vacuum freeze-drying. The content of polysaccharide in hot air drying was the lowest (5.4%), and the sensory evaluation was the lowest (4.4 points). Comprehensive appearance, nutritional composition and sensory evaluation, hot air-microwave combined drying was a drying method most suitable for edible fungi with mycelium constitutes tissue and large water content such as P. eryngii.